Adopting Hardware-In-the-Loop for Testing Vehicle Instrument Panel using Economical Approach - Wan Shahmisufi Wan Jamaludin; Tan Wei Ren; Bakhtiar Affendi Rosdi; Dahaman Ishak; Noor Hafizi Hanafi; Muhammad Nasiruddin Mahyuddin (Institute of Advanced Engineering and Science, 2018)
An economical approach for testing Vehicle Instrument Panel is proposed in this paper due to high expenditure of purchasing the available Commercial Off-The-Shelf Hardware-In-The-Loop. Vehicle Instrument Panel is designated as the Device-Under-Test in this paper. The Hardware-In-The-Loop, designated as the test equipment, will simulate the assigned input signals controllable via designed Graphical User Interface. The resulting display is shown on the Graphical User Interface and the Device-Under-Test. The speedometer gauge measurement showed the highest disparity of 4 km/h which is within the tolerance of the pre-determined specification of the Device-Under-Test.